Constellation and Rate Selection in Adaptive Modulation and Coding Based on Finite Blocklength Analysis and Its Application to LTE - Meng, Jin; Yang, En-Hui (IEEE transactions on wireless communications, 2014)
This paper tackles the constellation and channel coding rate selection problem in adaptive modulation and coding (AMC) for MIMO systems. Based on information theoretical results in finite blocklength analysis of channel capacity, a new selecting rule is proposed for narrow-band MIMO systems, and further extended to wide-band MIMO OFDM systems over channels subject to frequency-selective fading. When applied to Long Term Evolution (LTE) systems, the proposed selecting rule yields better performance in comparison with existing rules in the literature.